(untitled) (Global Journal of Management and Business Research, 2025)
Abstract- The purpose of this paper was to provide all individuals within leadership roles with an enriched comprehension of properly managing Generation Z This objective was fulfilled by the researcher conducting investigations on numerous articles and studies conducted by other specialists in the field of supervision and management The researcher also incorporated past experiences that were exhibited within organizations regarding how to properly manage employees who were considered Generation Z